Effects of Covid-19 restrictions on IPS service delivery in Northern Norway - S. Wittlund (European Psychiatry, 2022)
Introduction Individual Placement and Support (IPS) is an evidence-based supported employment program that helps people with severe mental illness to achieve steady meaningful employment in competitive mainstream jobs. Employment specialists are an integral part of IPS service delivery. The primary goal of an employment specialist is to help IPS users obtain competitive employment by providing targeted job development and ongoing support to workers and employers for as long as it is required.